Global Restriction of Using Antibiotic Growth Promoters and Alternative Strategies in Poultry Production. (March 2018) - Salim, Hossan MD.; Huque, Khan Shahidul; Kamaruddin, Kazi M.; Haque Beg, Anwarul
A growing global concern of antibiotic use in poultry diets due to its potential adverse effects on birds and human health, food safety and the environment has led to a complete ban or restricted use in some countries, and, at the same time, expanding options for the use of alternative feed additives. Multiple, rather than a single additive may replace antibiotic growth promoters (AGPs) in poultry. Blending of feeding additives and hygienic farm management, vaccination and biosecurity may help achieve good intestinal health, stabilise enteric ecosystems and result in sustainable and cost effective production performance of birds. Moreover, controlling unsolicited ingredients at the production level must have the support of different markets responsible for the supply of safe and quality poultry products for consumers. This requires the further increase and diversification of value added poultry products and the expansion of their markets through strategic planning and gradual limitation of live bird markets. More research is warranted in order to explore suitable, reliable and cost effective alternatives to AGPs for commercial use, and strategic poultry value chain development.